Introducing the Archive of Interwar Europe Election Data & Assemblies (AIEEDA) - Lea Kaftan; Bruno Della Sala; Olga Jerjomina; Stefan Stojkovic; Edoardo Alberto Viganò; Nils-Christian Bormann (Scientific Data)
Abstract We describe the Archive of Interwar Europe Election Data and Assemblies (AIEEDA), a new multi-level dataset of parliamentary elections in interwar Europe (1919-1939). The data contains electoral results for all parties that ran in 137 national parliamentary elections in 25 interwar European democracies. It further offers detailed time-invariant ideological and organizational variables for 401 parliamentary parties and 35 party alliances, along with time-variant data on their participation in 412 cabinets. Next to national-level election results, we provide disaggregated constituency/municipality-level results for Estonia, Ireland, Italy, Latvia, the Netherlands, and Yugoslavia. Having collected national and disaggregated data independently, we validated each through the other. We also provide linking tables to parliamentary election results at the constituency/municipality-level for France, Germany, and the United Kingdom. The archive will be useful to social scientists interested in testing theories on voting and party politics out of sample in a historical setting, or to use historical cases to understand contemporary phenomena such as the rise of radical right-wing parties.